ZAKAT SEBAGAI PENGURANG PENGHASILAN KENA PAJAK - ., Bambang Widarno (Universitas Slamet Riyadi, 2006)
Abstract TheÂ Indonesian is state with moslem majority resident. More than 200 million Indonesia resident, 80% confessing to believe in Islam, but did not mean that Indonesia is Islam state. Indonesia as according to its constitution represent secular state dissociating positive laws of political with religion law. Stipulating of law No. 38 Year 1999 about Management of Religious obligatory, Chapter IV section 14 is article 3 expressed that: